(untitled) (Indian Journal of Chemistry (IJC), 2025)
Here, we describe a simple synthetic strategy for the preparation of α-hydroxy, β-bromo-exo-dicyclopentadiene-1-one by following a 3-step sequence. The synthetic strategy rely on operationally simple reactions and high yielding steps. The newly synthesized compounds are characterized by NMR and HRMS data. The disclosed compound α-hydroxy, β-bromo-exo-dicyclopentadiene-1-one is similar to exo-dicyclopentadiene-1-one and it can be used a key building block to expand the chemical space of cyclopentanoids.